Perivascular spaces as a marker of disease severity and neurodegeneration in patients with behavioral variant frontotemporal dementia - Moses, Jasmine; Sinclair, Benjamin; Schwartz, Daniel L.; Silbert, Lisa C.; O’Brien, Terence J.; Law, Meng; Vivash, Lucy (Frontiers in Neuroscience, 2022)
Background: Behavioural Variant Frontotemporal Dementia (bvFTD) is a rapidly progressing neurodegenerative proteinopathy. Perivascular spaces (PVS) form a part of the brain’s glymphatic clearance system. When enlarged due to poor glymphatic clearance of toxic proteins, PVS become larger and more conspicuous on MRI. Therefore, enlarged PVS may be a useful biomarker of disease severity and progression in neurodegenerative proteinopathies such as bvFTD. This study aimed to determine the utility of PVS as a biomarker of disease progression in patients with bvFTD. Methods: Serial baseline and week 52 MRIs acquired from ten patients with bvFTD prospectively recruited and followed in a Phase 1b open label trial of sodium selenate for bvFTD were used in this study. The number and volume of PVS were detected using an automated algorithm and mixed models used to assess the relationship between PVS burden and other measures of disease (cognition, carer burden scale, protein biomarkers). Additional exploratory analysis investigated PVS burden in patients who appeared to not progress over the 12 months of selenate treatment (i.e., “non-progressors”). Results: Overall, PVS cluster number (ß=-3.27, CI [ -7.80 – 1.27], p=0.267) and PVS volume (ß=-36.8, CI [ -84.9 – 11.3], p=0.171) did not change over the paired MRI scans 12 months apart. There was association between cognition total composite scores and the PVS burden (PVS cluster ß=-0.802e-3, CI [9.45e-3 – -6.60e-3, p=<0.001; PVS volume ß=-1.30e-3, CI [-1.55e-3 - -1.05e-3], p=<0.001). There was a significant association between CSF t-tau and the number of PVS clusters (ß=2.845, CI [0.630 – 5.06], p=0.036). Within the “non-progressor” group (n=7), there was a significant relationship between the change in the CSF total-tau (t-tau) levels and the change in the PVS burden (PVS cluster (ß=1.46, CI [0.577 – 2.34], p=0.014; PVS volume ß=14.6, CI [3.86 – 25.4], p=0.032) over the trial period. Conclusion: Analysis of serial MRI scans 12 months apart in patients with bvFTD demonstrated a relationship between PVS burden and disease severity as measured by the total cognitive composite score and CSF t-tau. Further studies are needed to confirm PVS as a robust marker of neurodegeneration in proteinopathies.